2011
DOI: 10.1007/s11666-011-9667-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Thermophysical Properties of La2Zr2O7 Coatings by Thermal Spraying of an Amorphous Precursor

Abstract: Free-standing La 2 Zr 2 O 7 coatings were obtained by plasma spraying, using an amorphous La-O-Zr precursor as the feedstock. The La-O-Zr precursor powder was prepared by coprecipitation. During thermal spraying, the formation of coatings can be regarded as a joint process of melting-solidification, thermal decomposition, and crystallization. The time required for crystal growth was significantly shortened during spraying. Consequently, the average grain size of coatings was approximately 200 nm, with a narrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…[35] reported thermal conductivities of 0.73 to 0.79 W/(m·K) measured by the laser flash method for lanthanum zirconate coatings deposited by APS. The thermal conductivity was further reduced to ~0.42 W/(m·K) by using amorphous feedstock, due to a more uniform microstructure of the coatings and a higher porosity associated with the formation of nanopores [36]. Even though the given values are quite low compared to typical TBCs, they are higher than those reported in this study, mainly because of the difference in porosity between the coatings.…”
Section: Discussioncontrasting
confidence: 55%
“…[35] reported thermal conductivities of 0.73 to 0.79 W/(m·K) measured by the laser flash method for lanthanum zirconate coatings deposited by APS. The thermal conductivity was further reduced to ~0.42 W/(m·K) by using amorphous feedstock, due to a more uniform microstructure of the coatings and a higher porosity associated with the formation of nanopores [36]. Even though the given values are quite low compared to typical TBCs, they are higher than those reported in this study, mainly because of the difference in porosity between the coatings.…”
Section: Discussioncontrasting
confidence: 55%
“…These results indicated that it was necessary to use appropriately high amounts of molten salt to accelerate the LZO formation and phase pure LZO could be synthesized at 1100 °C with the salt/reactant weight ratio of 5:1. This synthesis temperature was much lower than required by CSSM (over 1500 °C) [8,9] and most of the wet-chemical techniques [5,11,14]. For example, Wang et al [5], Chen et al [11] and Kong et al [14] synthesized LZO nanopowders with various sizes at 1200 °C, from precursors derived from a sol-gel and/or co-precipitation process.…”
Section: Effect Of Salt Content On the Lzo Formationmentioning
confidence: 99%
“…This synthesis temperature was much lower than required by CSSM (over 1500 °C) [8,9] and most of the wet-chemical techniques [5,11,14]. For example, Wang et al [5], Chen et al [11] and Kong et al [14] synthesized LZO nanopowders with various sizes at 1200 °C, from precursors derived from a sol-gel and/or co-precipitation process. Based on these, it can be concluded that, compared to the sol-gel or co-precipitation method, the present MSS method not only lowered the synthesis temperature of LZO powders, but also simplified/shortened the overall preparation process.…”
Section: Effect Of Salt Content On the Lzo Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25] In recent years, the synthesis methods of La 2 Zr 2 O 7 have been received enormous attention in order to improve the properties of the La 2 Zr 2 O 7 and broaden the fields of its application. The methods include the conventional solid-state mixing method, 26,27 hydrothermal, 28 coprecipitation route, 29,30 combustion, 31 molten salt method, 32,33 sol-gel method, 34,35 and hydrazine method. 36 However, of these methods, the synthesis of La 2 Zr 2 O 7 materials usually requires tedious process (long reaction times), harsh condition (high temperatures and pressures), environmental hazardous, etc.…”
Section: Introductionmentioning
confidence: 99%